Membrane filtration: fouling and cleaning in forward osmosis, reverse osmosis, and ultrafiltration membranes - Siddiqui, F (2017)
A comparison of fouling in osmotically driven processes with that in pressure driven processes is the main focus of the thesis. Forward osmosis (FO) and reverse osmosis (RO) have received considerable attention for water treatment and seawater desalination. This research compared the nature of fouling in FO mode with that in RO starting with the same initial flux in connection with cleaning effects and then comparing to those in ultrafiltration membranes. In all cases, with cleaning as an integral part, the extent of fouling reversibility, and the question whether a critical flux could be determined were examined. The work during the first phase (undertaken at Oxford) quantified the removal of reversible fouling through rinsing by cold and hot water for a range of concentrations using the foulants dextran and carboxymethyl cellulose. The flux-TMP relationship was conventionally compared to that of the clean water flux. The later phase (at Singapore) compared the fouling in FO and RO by alginate in terms of multiple parameters using cellulose tri acetate (CTA) and thin film composite (TFC) membranes. Silica and alginate were selected as model foulants. Whilst experimental water flux profiles in the present study did not exhibit significant differences in trend between FO and RO fouling, foulant resistance for FO was found to be increasingly greater than for RO with the progression of the fouling tests. This was further corroborated by membrane autopsies post fouling tests; both foulant mass deposition density and specific foulant resistance for FO were greater than for RO. The analysis clearly revealed that FO is essentially more prone to fouling than RO which was presumably due to less flux decline in FO (or greater average flux) as compared to that in RO in result of ICP-self compensation effect which is opposite to the prevailing claim in the literature. Additionally, the present study did not find evidence that hydraulic pressure in RO has a role in foulant layer compaction. FO membrane fouling by real waters was the focus of the final phase of the research at SMTC. Pilot scale FO experiments were conducted on spiral wound CTA membrane with treated waste water obtained from a NEWater factory (Singapore) as the feed. In the second stage, experiments were repeated at bench scale with membrane coupons taken from the spiral wound membranes used earlier. The key finding was that the mass transfer coefficients in the Spiral-Wound module were around 50% lower than the corresponding values in the flat sheet unit and this severely limited the fluxes. The reason could be attributed to strong internal concentration polarisation in the former, where tightly wound spacers act to increase the structural parameter.